The Barfie handbook of pedagogical and scientific approaches to children's books and intercultural education - Morgado, Margarida (2010)
BARFIE (Books and Reading for Intercultural Education) is a European thematic network in intercultural education aimed at teachers, librarians, parents, children and school authorities that uses books and other media for children aged 6 to 16. BARFIE was developed in 2002, 2003 and 2004 with funding from the European Union as a Comenius network, involving at its core 14 European countries, with its teaching institutions, schools, libraries, and school authorities, while reaching out to involve schoolchildren, teachers, researchers, publishers and the public in general not only in those countries but all over Europe. BARFIE has developed a collection and catalogue of books for children and young people on intercultural education, which can be consulted at www.barfie.net and in book form. In the collection there are around 10 books from each of 14 European states that are members or partners of the BARFIE network. The books were carefully selected by experts on children’s books and young adult books, librarians, teachers and educators with the aim of developing ideas and concepts for teaching multiculturality, being European, fighting xenophobia and racism, integrating difference and celebrating similarities. Simultaneously, BARFIE developed an online catalogue of projects on intercultural education and children’s fiction, which pools together resources of European projects developed under the European Union framework, such as The Reader’s Corner. European Style Fairy Tales, at www.autopen.com/euro.fairy.shtml; Children’s Polar Library, at www.barnenspolarbibliotek.com/; Communicating tradition and culture across the internet: Traditional Tales at www.eurotales.eril.net; Europe of Tales, at www.europeoftales.net; Netlibris, at www.netlibris.net; and The European Picture Book Collection, at www.ncrcl.ac.uk/epbc/ . BARFIE further developed pedagogical materials to be used in connection with the books in the collection in the form of seminars for teachers on: Global Citizenship; Getting to Know Central European Countries through Their Books; the European Picture Book Collection; Netlibris International; or Art Basics for Children; A Handful of Stories. In order to reach schoolchildren and teachers BARFIE developed teaching packages at European and local levels on: Learning English as a Foreign Language through BARFIE books; Introducing Portuguese and the Portuguese Culture through BARFIE Books; the BARFIE Picture Book Collection, as well as introductory sessions on particular books of the collection for school use. Finally, BARFIE brought together teachers, librarians, and researchers on its three seminars: the first took place in Vienna and was hosted by the Austrian Ministry of Education and the Kinderliteraturhaus in Vienna; the second venue was Bratislava and the BARFIE seminar joined efforts with the Biennial of Illustration in Children’s Literature and IBBY in Slovakia; the third seminar was held in Warsaw and was sponsored by the IBBY section of Poland and the Polish National Library and the Austrian Kinderliteraturhaus. This collection of articles tells you more about BARFIE, its efforts, aims and achievements. It describes work done under BARFIE inspiration and the enthusiasm of teachers who were keen to take the BARFIE books into their schools and thus broaden national curricula into European spaces of communication, exchange and intercultural learning. It offers you pedagogical materials to work from, ideas to take back into libraries and schools, as well as resources to integrate with your teaching and living. The collection of articles also presents scientific and pedagogical frameworks to think about children’s books, reading and interactive learning in contemporary Europe. In the three sections of the collection – Using the Resources of the BARFIE Network (section 1), From Books into Other Media: Reading, Using & Performing, (Section 2), and Children’s Books and Children’s Literature – Research and Position Papers (section 3) there is material for you to use in the classroom, in the library or at home, as well as material to reflect on and to improve your professional practice. This collection does not, however, describe all BARFIE activities. You can find more about these on the BARFIE webpage, at www.barfie.net, through the BARFIE newsletters, as well as through the contact persons in each European country that are on the partner section of the BARFIE webpage. Feel free to use the BARFIE resources and to join our network!